Improving Knowledge About the Prevention of Acute Respiratory Infections in the Popubawo District of Jayawijaya Regency - Yoel Halitopo; Marleona Susana Sawamanay; Rohmani Rohmani; Katarina Farek Koten; Putri Ariani Kalepao; Emiana Lokobal (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2025)
Acute Respiratory Infections (ARI) remain a major health problem in the community, especially in the Papua Highlands. The prevalence of ARI among toddlers in Papua is among the highest in Indonesia, partly due to the community's lack of knowledge about ARI prevention and the implementation of Clean and Healthy Living Behaviours (PHBS). This community service activity aims to increase public knowledge about the prevention of respiratory tract infections in Waima Village, Popuoba District, Jayawijaya Regency. The method used is health education through counselling with slides and leaflets, accompanied by discussions and question and answer sessions. The target audience for this activity is the communities of Waima and Popuoba villages. The results of the activity show an increase in the community's understanding of the definition of ISPA, risk factors, modes of transmission, and efforts to prevent ISPA through the implementation of Clean and Healthy Living Behaviours (PHBS). The community showed enthusiasm and active participation during the event. This activity is expected to contribute to changes in public health behaviour, thereby reducing the risk of acute respiratory infections in the region.